Islamic Education Strategies To Counter Moral Decadence Among Vocational School Students - M. Zidni Abdul Jabar; Sofyan Hadi; Gunawan (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The increasing moral decadence among secondary school students—manifested through indiscipline, brawls, bullying, and disrespect for authority—poses a significant challenge for educational institutions. This study aims to explore the strategic role of Islamic Religious Education (IRE) teachers in addressing this moral decline through classroom-based interventions and external collaborations. Employing a qualitative case study approach, data were collected from eight informants, including school leaders, teachers, students, parents, and community figures. Techniques such as observation, interviews, and documentation were used, with data analyzed using the interactive model of Miles, Huberman, and Saldana, encompassing data collection, reduction, presentation, and conclusion drawing. Triangulation of sources and techniques was applied to ensure data validity. The findings reveal that IRE teachers adopt a combination of preventive and corrective strategies, including the imposition of educational sanctions such as reciting toyyibah (e.g., tahlil, istighotsah), performing istighfar writing tasks, and engaging students in school clean-up activities. Character development is fostered through habituation of akhlaqul karimah, such as honesty and mutual assistance. Furthermore, active collaboration with school administrators, counseling staff, parents, and community leaders enhances the effectiveness of these moral interventions. This study contributes to the discourse on character education by highlighting the integrative and community-based approach of IRE teachers in mitigating moral decline among adolescents.